1993
DOI: 10.1007/bf00327997
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of vascular endothelial growth factor on the chicken chorioallantoic membrane

Abstract: The effect of vascular endothelial growth factor (VEGF165) on the chorioallantoic membrane (CAM) of 13-day-old chick embryos was studied. The factor was applied in doses of 0.5-4 micrograms for a period of up to 4 days. Macroscopical, histological and immunohistological studies were carried out. The localization of the factor was examined with an anti-VEGF antibody. The mitogenicity of VEGF165 and basic fibroblast growth factor (bFGF) were studied by means of the BrdU-anti-BrdU method. Furthermore, the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 33 publications
4
85
0
2
Order By: Relevance
“…The observation of a fourfold increase in N, as compared with the controls could be expected and corresponds to the difference in LI of 34% (VEGF) against 7% (control) as reported by Wilting et al (1993). The completely changed distribution, however, was surprising.…”
Section: Effects Of Vegfsupporting
confidence: 75%
“…The observation of a fourfold increase in N, as compared with the controls could be expected and corresponds to the difference in LI of 34% (VEGF) against 7% (control) as reported by Wilting et al (1993). The completely changed distribution, however, was surprising.…”
Section: Effects Of Vegfsupporting
confidence: 75%
“…Differences between various controls or between various VEGF isoforms were not significant. We conclude that (1) the carrier material was well suited for the CAM assay because it did not induce changes of the vascular pattern as compared with the situation when no carrier was present; (2) the endothelium-specific mitogenic effect of the 165 (Wilting et al, 1993 and 121 (Wilting et al, 1996) amino acid isoforms induced a greater complexity of the vascular pattern at the site of application, which corresponded to the histologically verified multiple layers of capillaries and precapillary vessels, and to the visual impression of a higher bifurcation density; (3) the XCM was superior to the BCM because of its stability and reduced variance. …”
Section: Complexity Of Cam Blood Vessel Pattern Is Increased By Vegfmentioning
confidence: 96%
“…This can be verified by time-consuming histological techniques, or much faster by image analysis of the altered vessel arrangement in whole mounts. For details on CAM structure and histology, and on the CAM assay for angiogenesis, the reader is referred to Wilting et al (1993Wilting et al ( , 1996, and references therein, and to Kurz et al (1994, 1995). We here provide only brief information in specimens and growth factors.…”
Section: Application To Angiogenesis Researchmentioning
confidence: 99%
“…The former has been implicated in vascular remodeling within adult tissues (Maisonpierre et al, 1997), whereas the latter is known to be essential for pericyte recruitment in the retina (Benjamin et al, 1998), brain (Hellstrom et al, 1999, and placenta (Ohlsson et al, 1999). Notably, the application of PDGF-B to fully developed CAMs leads to an abundant formation of larger pre-and postcapillary microvessels but does not amplify capillary meshes (Oh et al, 1998), whereas exogenous VEGF-A affects the capillary plexus and terminal feeding vessels, but has no influence on larger microvessels (Wilting et al, 1993;Kurz et al, 1995). Our assumption that endothelial cells respond to local challenges when initiating IBR is strongly supported by two recent observations: endothelial grafting in the chick-quail system showed that expression of the arterial marker ephrin-B2 depends on hemodynamics or local environment (Othman-Hassan et al, 2001); and serial section histology demonstrated intussusceptive remodeling in conditions of severely altered blood flow during tissue repair or tumor angiogenesis (Patan et al, 2001a,b).…”
Section: Possible Molecular Mechanisms Involved In Vascular Remodelingmentioning
confidence: 99%